Iron overload triggers mitochondrial fragmentation via calcineurin-sensitive signals in HT-22 hippocampal neuron cells. (4th November 2015) - Park, Junghyung; Lee, Dong Gil; Kim, Bokyung; Park, Sun-Ji; Kim, Jung-Hak; Lee, Sang-Rae; Chang, Kyu-Tae; Lee, Hyun-Shik; Lee, Dong-Seok
Graphical abstract: Highlights: FAC-induced iron overload promotes neuronal apoptosis. Iron overload causes mitochondrial fragmentation in a Drp1-dependent manner. Iron-induced Drp1 activation depends on dephosphorylation of Drp1(Ser637). Calcineurin is a key regulator of Drp1-dependent mitochondrial fission by iron. Abstract: The accumulation of iron in neurons has been proposed to contribute to the pathology of numerous neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease. However, insufficient research has been conducted on the precise mechanism underlying iron toxicity in neurons. In this study, we investigated mitochondrial dynamics in hippocampal HT-22 neurons exposed to ferric ammonium citrate (FAC) as a model of iron overload and neurodegeneration. Incubation with 150 μM FAC for 48 h resulted in decreased cell viability and apoptotic death in HT-22 cells. The FAC-induced iron overload triggered mitochondrial fragmentation, which was accompanied by Drp1(Ser637) dephosphorylation. Iron chelation with deferoxamine prevented the FAC-induced mitochondrial fragmentation and apoptotic cell death by inhibiting Drp1(Ser637) dephosphorylation. In addition, a S637D mutation of Drp1, which resulted in a phosphorylation-mimetic form of Drp1 at Ser637, protected against the FAC-induced mitochondrial fragmentation and neuronal apoptosis. FK506 and cyclosporine A, inhibitors of calcineurin activation, determined that calcineurin was associated with the iron-induced changes in mitochondrial morphology and the phosphorylation levels of Drp1. These results indicate that the FAC-induced dephosphorylation of Drp1-dependent mitochondrial fragmentation was rescued by the inhibition of calcineurin activation. Therefore, these findings suggest that calcineurin-mediated phosphorylation of Drp1(Ser637) acts as a key regulator of neuronal cell loss by modulating mitochondrial dynamics in iron-induced toxicity. These results may contribute to the development of novel therapies for treatment of neurodegenerative disorders related to iron toxicity.